Sub-clinical atherosclerosis in the common carotid artery in women with/without previous pre-eclampsia: A seven-year follow-up. (November 2019) - Akhter, Tansim; Larsson, Anders; Larsson, Marita; Naessen, Tord
Abstract: Background and aims: Pre-eclampsia is associated with increased risk of cardiovascular disease and premature death. However, conventional common carotid artery intima-media thickness (CCA-IMT) measurement does not reflect this. In contrast, measurement of the individual CCA intima and media thicknesses clearly indicates increased vascular risk both at diagnosis and about one year after pre-eclampsia. This study examined whether individual CCA wall layers, risk factors for cardiovascular disease, and markers of endothelial dysfunction had normalized or remained unfavorable seven years after pre-eclampsia. Methods: The individual CCA intima and media thicknesses were measured using 22 MHz ultrasound. Conventional cardiovascular risk factors were recorded. A thick intima, thin media and high intima/media thickness ratio (I/M) are signs of sub-clinical atherosclerosis. Results: The median age of women with previous pre-eclampsia (cases = 23) or normal pregnancies (controls = 35) was 39/37 years. At follow-up (median about seven years), the intima remained thicker and the I/M was higher in cases than in controls [all p < 0.0001; p < 0.001 after adjustment for time to follow-up, body mass index (BMI), and mean arterial pressure (MAP)], whereas the CCA-IMT was illogically thinner. Further, BMI, MAP, hip circumference, abdominal height, serum endostatin and apolipoprotein B levels were higher in cases (all p < 0.05). Intima and I/M measurements were correlated with age, MAP, endostatin and apolipoprotein B, whereas no logical correlations were found for CCA-IMT. Conclusions: The arteries in cases but not controls were still adversely affected after seven years. Measuring intima thickness and I/M appears preferable to measuring CCA-IMT for demonstrating vascular risk after pre-eclampsia. Graphical abstract: Image 1 Highlights: Substantially affected arteries at follow-up 7 years after preeclamptic pregnancy. Artery wall layer dimensions associated with CVD-risk factors and vascular inflammation. In line with the documented increased risk of CVD later in life in pre-eclampsia.